Computational studies on the binding mechanism between triazolone inhibitors and Chk1 by molecular docking and molecular dynamics. Issue 1 (5th November 2014) - Lv, Min; Ma, Shuying; Tian, Yueli; Zhang, Xiaoyun; Lv, Wenjuan; Zhai, Honglin
Abstract : The 3D inhibitor–protein interaction diagram of (a) the Chk1–5a complex (Δ G pred = −45.64 kcal mol −1 ) and (b) the Chk1–31 complex (Δ G pred = −35.28 kcal mol −1 ) obtained from molecular dynamics simulations. Abstract : Chk1, a serine/threonine protein kinase that participates in transducing DNA damage signals, is an attractive target due to its involvement in tumor initiation and progression. As a novel Chk1 inhibitor, the triazolone's bioactivity mechanism is not clear. In this study, we carried out an integrated computational study that combines molecular docking, molecular dynamics (MD) simulations, and binding free energy calculations to identify the key factors necessary for the bioactivities. With the aim of discerning the structural features that affect the inhibitory activity of triazolones, MK-8776, a Chk1 inhibitor that reached the clinical stage, was also used as a reference for simulations. A comparative analysis of the triazolone inhibitors at the molecular level offers valuable insight into the structural and energetic properties. A general feature is that all the studied inhibitors bind in the pocket characterized by residues Leu14, Val22, Ala35, Glu84, Tyr85, Cys86, and Leu136 of Chk1. Moreover, introducing hydrophobic groups into triazolone inhibitors is favorable for binding to Chk1, which is corroborated by residue Leu136 with a relatively large difference in the contribution betweenMK-8776 and five triazolones to the total binding free energies. A hydrogen bond between the polar hydrogen atoms at R1 and Cys86 can facilitate proper placement of the inhibitor in the binding pocket of Chk1 that favors binding. However, the introduction of hydrophilic groups into the R2 position diminishes binding affinity. The information provided by this research is of benefit for further rational design of novel promising inhibitors of Chk1.